2017
DOI: 10.1186/s12889-017-4193-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving immunization in Afghanistan: results from a cross-sectional community-based survey to assess routine immunization coverage

Abstract: BackgroundDespite progress in recent years, Afghanistan is lagging behind in realizing the full potential of immunization. The country is still endemic for polio transmission and measles outbreaks continue to occur. In spite of significant reductions over the past decade, the mortality rate of children under 5 years of age continues to remain high at 91 per 1000 live births.MethodsThe study was a descriptive community-based cross sectional household survey. The survey aimed to estimate the levels of immunizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
27
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 23 publications
12
27
2
Order By: Relevance
“…The percentage of non-vaccinated children in the rural areas of Afghanistan was higher than in urban areas. Similar findings were presented by a study in 2013 among Afghan children age 12-23 months, where the prevalence of full vaccination was found to be 62% in urban areas versus 49% in rural areas [17]. These findings were consistent with studies conducted in Pakistan [4], India [18], and Ethiopia [24].…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…The percentage of non-vaccinated children in the rural areas of Afghanistan was higher than in urban areas. Similar findings were presented by a study in 2013 among Afghan children age 12-23 months, where the prevalence of full vaccination was found to be 62% in urban areas versus 49% in rural areas [17]. These findings were consistent with studies conducted in Pakistan [4], India [18], and Ethiopia [24].…”
Section: Plos Onesupporting
confidence: 90%
“…Understanding factors that influence vaccination coverage is important to increase the vaccination coverage rate. Numerous investigations have found that the factors influencing vaccination coverage among children include sex of child, place of birth, maternal and paternal education, maternal and paternal occupation, number of antenatal care (ANC) visits, household characteristics, and sociocultural factors [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the poorest and poorer mothers were less likely to have a fully vaccinated child. Similar findings have reported on the association between lower socio-economic status and the lesser likelihood of a fully vaccinated child (8,12,41,42). One explanation was that poorer mothers had less time or "multiple livelihood activities which deter clinic attendance" (43).…”
Section: Socio-economic Status and Healthcare Utilizationsupporting
confidence: 73%
“…Consequently, the region may witness a setback in the advances made in polio eradication and measles elimination as a result of low vaccination coverage and breakdown of surveillance systems. Polio endemicity in Pakistan, Afghanistan and Nigeria is partly attributed to the protracted armed conflict in these countries [32,33].…”
Section: Discussionmentioning
confidence: 99%